A comparative study on ingredient and efficiency difference between fresh and steamed Gastrodia elata Blume: An herbal material to a novel functional food. (July 2021) - Ma, Ji; Deng, Yang; Wang, Yuqin; Liu, Qiuyan; An, Jing; Li, Maoru; Song, Nali; Zhang, Ju; Cheng, Lijun; Ma, Kejian
Graphical abstract: Highlights: Over 19 ingredients difference were investigated and compared between two GE samples. 3 of the major bioactive ingredient of GE including GAS、HBA and PA were investigated and compared in vivo. 2 animal models were conducted to investigate the efficiency of two GE samples. Tryptophan related metabolites pathway were found to be the potential mechanism of efficiency difference. Abstract: Gastrodia elata Blume (GE) is an orchid herbal material widely used in China for thousands of years. Recently, the Chinese government has noted that GE can be legally used as functional food, which brings a huge food market for GE. The processing of herbal materials is considered to be the most critical technology to ensure quality and efficacy. Proper processing can transform raw materials into food or drugs with appropriate ingredients and functions. However, due to the unprocessed or the fresh GE can be easily bought in the market, the ingredient and efficiency difference between fresh and processed GE need to further investigate. Based on the understanding of the mechanism of processing in the GE and its possible application in the dietary treatment for anxious people, this paper studied the ingredient changes of the main active constituents of the GE before and after processing. Meanwhile, blood concentrations of three active ingredient including gastrodin (GAS), p -hydroxylbenzyl alcohol (HBA) and Parishin were investigated. Moreover, the different efficacy of the GE in various animal models and the potential mechanisms were studied. Finally, water steamed GE showed distinct better bioactivity than the fresh GE. Further mechanism based on the metabolomics was investigated. The difference of tryptophan related metabolites was observed and discussed to be the possible cause of the increasing bioactive efficiency in GE with steaming process.